Penggunaan Media Ular Tangga pada Pembelajaran Tata Cara Sholat di Taman Pendidikan AL-Qur’an - Syah Putra, Calvin Surya; Nadlif, Ainun (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
This research is motivated by the use of learning media on prayer procedures that have not been maximized, thus causing students' incomprehension of the sequence of prayer procedures. Therefore, researchers try to use learning media in the form of Snakes and Ladders media which has advantages that can produce an interesting and interactive atmosphere for the learning process. The purpose of this study is to assess whether the use of snakes and ladders media can improve students' understanding of the basic sequence of basic prayers and student participation in prayer activities at TPQ Darul Taqwa Ganting Sidoarjo. This research uses descriptive qualitative method, the sample in this research is TPQ Darul Taqwa students. The results showed that the ability to understand the prayer procedures increased and significantly by using snakes and ladders media. The ability to understand the prayer procedures is shown by students with the ability to remember the prayer sequence when the educator asks to practice it.